Modelling of The Effect of Waste Management in Ikeja Area of Lags State Nigeria - Taiwo S. Amosun; Wasiu Oyediran Adedeji (Borobudur Engineering Review, 2022)
There is no doubt that waste in all ramifications disturbs the balance of nature. As a result of this, it will be of great importance to mankind if a way is devised to foretell how the effectiveness or otherwise of waste management can affect the lives of those living in an area. This work considers waste management in a holistic view and attempts to develop a model for the relationship between waste management/disposal method and its effect on the people living within a defined geographical location. Lagos which has a relatively high daily per capital domestic waste generation rate in Nigeria has not yet established a comprehensive waste management system. A municipal solid waste management is designed based on Nigerian situations at the end of which a model y=-0.6228x + 56.31 was obtained. This predicts that as waste disposal method becomes appropriate and adequate, the occurrence of different types of diseases decreases rapidly. This may be a very useful tool of waste management for the Government and an easier means of ensuring a healthier living environment for the masses.